2018
DOI: 10.1016/j.jvs.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tear Distance From Left Subclavian Artery Predicts Growth in Chronic Type B Aortic Dissection

Abstract: dissection [CD]). SAI procedures were grouped into open (intended treatment zone or remote aortic site), major endovascular (TEVAR extension or endograft implanted at noncontiguous aortic site), and minor endovascular (side branch or false lumen embolization) categories. Kaplan-Meier methodology was used to estimate freedom from SAI and survival. Cox proportional hazards modeling was used to identify predictors of SAI. Results: A total of 258 patients underwent TEVAR for AD (49% [n ¼ 128]) and CD (51% [n ¼ 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, a FL diameter of >22 mm and the location of the FL on the greater curve of the aorta have also been shown to be predictive of aneurysm growth (38)(39)(40). Studies attempting to characterize the primary intimal tear have suggested that size ≥10 mm or location in close proximity to the left subclavian artery in Zone 3 are independent predictors of aneurysm formation (28,40). Despite this progress, there is no single radiographic feature that reliably predicts aortic growth and death.…”
Section: Management Of Uncomplicated Tbad: Evolving Role Of Tevar and Ongoing Areas Of Controversymentioning
confidence: 99%
“…Additionally, a FL diameter of >22 mm and the location of the FL on the greater curve of the aorta have also been shown to be predictive of aneurysm growth (38)(39)(40). Studies attempting to characterize the primary intimal tear have suggested that size ≥10 mm or location in close proximity to the left subclavian artery in Zone 3 are independent predictors of aneurysm formation (28,40). Despite this progress, there is no single radiographic feature that reliably predicts aortic growth and death.…”
Section: Management Of Uncomplicated Tbad: Evolving Role Of Tevar and Ongoing Areas Of Controversymentioning
confidence: 99%